JENIS-JENIS BAKTERI POTENSIAL PATOGEN PADA IKAN PATIN (Pangasius sp) DI KOLAM BUDIDAYA IKAN AIR TAWAR KOTA BELING TANAH AIR KECAMATAN TANJUNG ANOM PROVINSI SUMATERA UTARA - Fransiska Falentina Naibaho; Dwi Suryanto; Rusdi Leidonald (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2018)
Catfish (Pangasius sp) is the most widely cultured fish in the aquaculture activities. One problem in fish culture is disease caused by bacteria. Fish samples were taken from Tanjung Anom district. The aim of this study was to know the potensial bacterial pathogens that cause infection in catfish.This study was held from July to August 2017 in BKIPM Laboratory of Class I Medan I. The isolation and characterization of bacterial pathogen of the catfish was performed by using dilution method and spread method. The organs target for isolation of pathogenic bacteria were kidney, liver and water. The result showed that Aeromonas salmonicida, Aeromonas sobria, Aeromonas caviae and Yersenia sp. were found as potential pathogenic bacteria.Keywords : Pangasius sp, Aquaculture pond, Bacterial Pathogens